David remembered : kingship and national identity in ancient Israel - Blenkinsopp, Joseph, 1927-2022 (Cambridge , Wm .B. Eerdmans Publishing Co, 2013)
Examines the David theme in the collective mind of ancient Israel and the early church. In this follow-up study to Judaism, The First Phase, Joseph Blenkinsopp traces the development of traditions about David in the collective memory of the people of Israel and the first Christians, from the extinction of the Davidic dynasty in the sixth century B.C.E. to the early common era. David Remembered is neither a biography of David nor an exegetical study of the biblical narrative about David. Rather, it focuses on the memory of David as a powerful factor in the formation of social identity, in political activity (especially in reaction to imperial rule), and in projections of the future viewed as the restoration of a never-forgotten past. -- Publisher's website
1. The eclipse of the House of David -- The final Phase (609-586 B.C.E.) -- Josiah the incomparable -- The end of the line -- 2. After the disaster: the Benjamin-Saul alternative -- Surviving the disaster -- Judah and Benjamin: different approaches to imperial Babylon -- Saul -- 3. Under the yoke of Babylon: the Gedaliah episode -- The Shaphan family and Jeremiah -- The appointment and assassination of Gedaliah -- 4. The theological politics of Deutero-Isaiah -- Coping with catastrophe -- Tokens of faithful love to David -- The historical context: prospects and options -- Cyrus, divinely inspired and divinely appointed successor to the Davidic line -- The international context of Deutero-Isaiah's endorsement of Cyrus -- 5. Zerubbabel -- Who was Zerubbabel? -- Zerubbabel and the new temple -- A cosmic upheaval and the reign of Zerubbabel foretold -- Zerubbabel and the crisis of the Persian empire -- An urgent summons to leave Babylon (Zechariah 2:10-13[6-9]) -- Joshua, high-priest designate, and the presentation of "Branch" (Zechariah 3:1-8, 9b-10) -- The stone with seven eyes (Zechariah 3:9a, 4:4-5, 11-14) -- The secret coronation of Zerubbabel (Zechariah 6:9-15) -- What happened in the house of Josiah ben Shephaniah? --
Includes bibliographical references (pages 182-196) and indexes
Keywords: David, -- King of Israel -- Family; Bible. -- Criticism, interpretation, etc; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Jews -- History -- 586 B.C.-70 A.D; Monarchy